Pengaruh Edukasi Audio-Visual dan Leaflet terhadap Pengetahuan Keluarga tentang Deteksi Dini dan Pertolongan Pertama Stroke di Puskesmas Tamamaung - Nur Muhardiana Mardin; Muzakkir Muzakkir; Asriyanti Asriyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stroke is one of the leading causes of death and long-term disability worldwide. Early detection and prompt first aid during the golden period are essential to improve patient outcomes, yet family knowledge regarding stroke management is often limited. This study aimed to analyze the effect of health education media, specifically audio-visual and leaflet, on family knowledge of early detection and first aid for stroke patients in the working area of Tamamaung Public Health Center, Makassar. This study used a quasi-experimental design with a two-group pre-test post-test approach. A total of 64 respondents were selected using purposive sampling and divided into audio-visual and leaflet groups. Data were collected using a structured questionnaire and analyzed using the Wilcoxon and Mann-Whitney tests. The results showed a significant increase in knowledge in both groups after the intervention (p = 0.000), with a significant difference between groups (p = 0.016), where audio-visual media was more effective than leaflets. These findings indicate that both media improve family knowledge, but audio-visual media is more effective and can be recommended as a primary educational tool to improve family preparedness in stroke emergencies.